(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2015)
This paper offers an analysis about the issue of off-label drugs use in Italy, focusing on the sport area and on the role of the State. In particular interconnections and divergences with anti-doping regulation will be addressed, making some reflections about the partial lack of regulation.